(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2017)
The glorious days of the Sultanate of Aceh Darussalam during the 17th century gave rise to a form of writing that specifically provided advice and guidance on governance to the king and officials, or Mirrors for Rulers, namely Taj al-Salatin (1604) and Bustan al-Salatin (1638). Copies of which were composed during the reign of Sultan Alauddin Riayat Shah (1589-1604), Sultan Iskandar Muda Mahkota Alam (1606-1636) and Sultan Iskandar Thani (1636-1641) characterized the greatness of the civilization and political power possessed by the Sultanate of Aceh then. However, the position of Taj al-Salatin as the earliest Mirrors for Rulers in Aceh can now be challenged by the discovery of two Nasihat al-Muluk manuscripts, written by Imam al-Ghazali and Sheikh Hussain Wa’iz al-Kashifi, bringing the total to four works in the Malay literary history. All four copies of the Jawi manuscripts hold their own unique traits. Keywords: Sultanate of Aceh Darussalam, Mirrors for Rulers, Taj al-Salatin, Bustan al-Salatin and Nasihat al-Muluk, Malay literary history, Jawi manuscripts